PENGEMBANGAN BAKAT, KEILMUAN, DAN SEMANGAT BELAJAR SISWA DI SDN LEMBA - muh irwan; Hasbi Ibrahim; Rezki Awalia; Muhben Muktar; Nahda Syaidah Marhabatsar; Alda Robiany; Moh. Hidayat (PPM LP2M UIN Alauddin Makassar, 2022)
Porseni or commonly referred to as sports and arts week, is a forum where we can channel interests, talents and hobbies, especially students, with the aim of strengthening student relationships both from seniors to juniors and teachers, apart from that, the purpose of this research is to train talent development. and enthusiasm for students learning, especially in SD 03 Lemba. This study uses a qualitative approach with a Phenomenological and Observational research model. The findings of this study are as follows: 1) The condition of students’ skills is different because it is influenced by the family because it is influenced by the family environment, especially in the religious field. 2)There is a KKN student work program that can develop students’ scientific talent skills and enthusiasm for learning, including art porn. 3) KKN students hold this activity to develop students’ scientific talent skills and enthusiasm for learning which is proven through changing student behavior to be active and better. 4) The obstacle experienced by the activity was the lack of competition, so the competition was limited because it was still during the covid-19 pandemic. This work program activity was carried out for four days and the efforts made were by good communication, making the concept of a competition about religion interesting, continuing to carry out health protocols, and closing the prosenin activity followed by vaccination in collaboration with Mrs. Bhayangkari, Soppeng Regency. This work program was successfully carried out with full support by education and education staff and was closely monitored by the Covid-19 sitgam Team in Soppeng Regency.